(untitled) (Pedagogical Horizons, 2025)
The article presents existential pedagogy as an approach to adequately teaching democratic principles, such as the free development of personality, in school lessons. This teaching and learning theory is based on the principles of Alfried Längle’s existential analysis and thus also on Viktor Frankl’s underlying logotherapy. For both, the focus is on the individual and their relationship to their life. Using an example from school practice (the transfer of an 11-year-old transgender child with autistic traits to a new school), the article describes how an inclusive approach, taking into account the principles of existential pedagogy, contributes to the understanding of the entire class regarding the importance of diversity and subjectivity as the basis for democratic coexistence.